2014
DOI: 10.4049/jimmunol.1400871
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasomes Shape the Transcriptome and Regulate the Function of Dendritic Cells

Abstract: By regulating protein degradation, constitutive proteasomes (CPs) control practically all cellular functions. In addition to CPs, vertebrates express immunoproteasomes (IPs). The major nonredundant role ascribed to IPs is their enhanced ability to generate antigenic peptides. We report that CPs and IPs differentially regulate the expression of >8000 transcripts in maturing mouse dendritic cells (DCs) via regulation of signaling pathways such as IFN regulatory factors, STATs, and NF-κB. IPs regulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 56 publications
(60 reference statements)
1
37
0
Order By: Relevance
“…To evaluate the role(s) of IPs in mTEC biology, we compared the thymi of WT mice to those of mice with targeted inactivation of genes encoding two IP subunits (Psmb8 and Psmb10; hereafter referred to as double-knockout [dKO] mice). Because of the cooperative rules of IP catalytic subunit assembly, cells from these mice are almost totally IP deficient, because in addition to the total lack of PSMB8 and PSMB10, they contain low levels of PSMB9 ( Figure S3B) (de Verteuil et al, 2014). Consistent with a previous report (Kincaid et al, 2011), we found that the frequency of CD8 single-positive thymocytes was decreased in dKO mice relative to WT mice ( Figure 2B).…”
Section: Ips Selectively Regulate Mtec Cellularity In a Cell-autonomosupporting
confidence: 91%
See 1 more Smart Citation
“…To evaluate the role(s) of IPs in mTEC biology, we compared the thymi of WT mice to those of mice with targeted inactivation of genes encoding two IP subunits (Psmb8 and Psmb10; hereafter referred to as double-knockout [dKO] mice). Because of the cooperative rules of IP catalytic subunit assembly, cells from these mice are almost totally IP deficient, because in addition to the total lack of PSMB8 and PSMB10, they contain low levels of PSMB9 ( Figure S3B) (de Verteuil et al, 2014). Consistent with a previous report (Kincaid et al, 2011), we found that the frequency of CD8 single-positive thymocytes was decreased in dKO mice relative to WT mice ( Figure 2B).…”
Section: Ips Selectively Regulate Mtec Cellularity In a Cell-autonomosupporting
confidence: 91%
“…Nuclear factor kB (NF-kB) and tumor necrosis factor signaling regulate mTEC differentiation, and mice deficient in receptor activator of nuclear factor-kB (RANK), CD40, or LTbR have a small thymic medulla and develop autoimmunity (Akiyama et al, 2008;Chin et al, 2003). Because IPs and CPs differentially regulate the activation of these signaling pathways (de Verteuil et al, 2014), we surmised that mTEC defects in dKO mice could result from dysregulated mTEC differentiation. We therefore isolated mTEC lo and mTEC hi from WT and dKO mice and analyzed the mRNA expression profiles of genes that control mTEC differ-entiation and thymic medulla formation.…”
Section: Mature Mtecs From Ip-deficient Mice Have a Reducedmentioning
confidence: 99%
“…RNA extraction and high-throughput RNA-seq RNA extraction and RNA-seq were performed as described (25,26). Output data were mapped to the Mus muculus (mm10) reference genome using ELANDv2 alignment tool from the CASAVA 1.8.2 software, and transcript levels were expressed as reads per kilobase of exon per million mapped reads (RPKM) (27).…”
Section: Flow Cytometry and Cell Sortingmentioning
confidence: 99%
“…Until now, it is unresolved how these changes in immune cell function are mediated. Immunoproteasome deficiency has been shown to influence the transcriptome of immune cells, which might be the result of altered substrate turnover in immunoproteasome-deficient cells (57,112,113). One explanation might be that immunoproteasomes increase the general pool of proteasomal catalytic capacity (50).…”
Section: Immunoproteasomes Shape Immune Cell Function and Innate Immumentioning
confidence: 99%